2009
DOI: 10.1242/dmm.001941
|View full text |Cite
|
Sign up to set email alerts
|

Rodent models of diabetic cardiomyopathy

Abstract: Diabetic cardiomyopathy increases the risk of heart failure in individuals with diabetes, independently of co-existing coronary artery disease and hypertension. The underlying mechanisms for this cardiac complication are incompletely understood. Research on rodent models of type 1 and type 2 diabetes, and the use of genetic engineering techniques in mice, have greatly advanced our understanding of the molecular mechanisms responsible for human diabetic cardiomyopathy. The adaptation of experimental techniques … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
200
2
6

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 248 publications
(216 citation statements)
references
References 177 publications
8
200
2
6
Order By: Relevance
“…We set out to determine the redox effects of β 3 AR stimulation in experimental hyperglycemia and it was important to first examine whether diabetes‐inducing agents have confounding effects on the target proteins of interest. The most commonly used diabetogenic agent STZ, a glucosamine‐nitrosourea taken up by pancreatic β cells causing their necrosis,30 decreased the oxidative modification of β 1 Na + ‐K + pump subunit in vitro. With short in vitro exposure time, this is likely due to the property of STZ to release NO,31 shown to reduce β 1 subunit glutathionylation 11.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We set out to determine the redox effects of β 3 AR stimulation in experimental hyperglycemia and it was important to first examine whether diabetes‐inducing agents have confounding effects on the target proteins of interest. The most commonly used diabetogenic agent STZ, a glucosamine‐nitrosourea taken up by pancreatic β cells causing their necrosis,30 decreased the oxidative modification of β 1 Na + ‐K + pump subunit in vitro. With short in vitro exposure time, this is likely due to the property of STZ to release NO,31 shown to reduce β 1 subunit glutathionylation 11.…”
Section: Discussionmentioning
confidence: 99%
“…With short in vitro exposure time, this is likely due to the property of STZ to release NO,31 shown to reduce β 1 subunit glutathionylation 11. When administered at high toxic doses in vivo, STZ increases cellular ROS levels and causes undesirable extrapancreatic genotoxic effects that further complicate differentiation of STZ direct molecular effects from effects of diabetes that it induces 30. Alloxan, the second most commonly used diabetogenic agent, increased β 1 pump subunit glutathionylation both in vitro and in vivo independently of diabetogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No animal model is perfect, and current rodent models of type 2 diabetes have been shown to have some limitations (reviewed by Bugger and Abel). 4 Most of these models comprise of transgenic animals which are expensive to maintain and also fail to mimic the multifactorial disease pathogenesis process. 5 A rat model first proposed by Reed et al, 6 and later modified by Srinivasan et al, 7 aimed to induce type 2 diabetes using high-fat diet (HFD) resulting in peripheral insulin resistance, followed by a low dose of the pancreatic β-cell toxin, streptozotocin (STZ).…”
Section: Introductionmentioning
confidence: 99%
“…Investigation revealed that patients with diabetes mellitus (DM) were more likely to suffer from coronary artery disease, hypertension and mortality following myocardial infarction (7,8), while DC was one of the most common serious cardiovascular complications of DM (9). Cellular metabolic abnormalities and defections of organelles were shown to participate in the pathology of DC (10)(11)(12)(13)(14), which is a chronic and complex process associated with impaired calcium homeostasis, increased lipid uptake, myocardial insulin resistance, glucotoxicity, increased oxidative stress and activation of the renin-angiotensin system (15). Furthermore, the pathological role of endoplasmic reticulum (ER) stress in DC has been noted in a number of studies (16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%